A NOTE ON FRANCISCODENDRON HYLAND & STEENIS (STERCULIACEAE) - KOSTERMANS, A.J.G.H. (REINWARDTIA, 1988)
Franciscodendron Hyland & van Steenis {in Burnonia 10: 211-214. 1987) is, as stated by the authors related to Hildegardia because of its samara-like, indehiscent, one-to two-seed papyraceous (when mature) fruit (differing by the stelate pilose seeds).